Periorbital infection and fistula after placement of zygomatic implants: a case report and review - Bento de Queiroz, Sormani; Guilherme Farina, Cassius; Jaqueline Alves do Nascimento (Brazilian Journal of Case Reports, 2022)
Zygomatic implants are a good alternative to severely atrophic maxilla prosthetic treatment, but complications can result from their placement. Skin fistulas are extremely rare complications of zygomatic implants, but it’s management can be challenging. Skin complications can happen when the apex of the zygomatic implant protrudes above the limits of zygomatic bone. To prevent its occurrence, careful planning must be done. The surgeon must control the final position of the implant at the appropriate length carefully. If infection or cutaneous fistula occurs, surgery to cut off the apex of the implant is indicated, either intra- or extra-orally. The aim of this case report was to describe the case of cutaneous fistula after Quad Zygoma treatment of extreme maxillary bone atrophy. A 56-year-old woman developed a left periorbital fistula 4 months after the placement of 4 zygomatic implants. Implant apex was palpable under the skin of zygomatic bone body. We opted for extra-orally cut off the implant tip above the outer cortical of the zygomatic bone. Postoperative course was uneventful and the patient had no more signs and symptoms of infection or fistula.